Prevalence and correlates of COVID-19 vaccine hesitancy among the elderly in Qatar: A cross-sectional study - Mustafa Abdul Karim (14159016) (2022)
Older individuals are more vulnerable to severe coronavirus disease 2019 and medical complications. Vaccination stands as an efficient and safe vanguard against infection. However, negative attitudes and perceptions pertaining to available vaccines might hinder community inoculation. The aim of this study was to assess vaccine hesitancy and its psychosocial determinants among the elderly in Qatar. We conducted a cross-sectional study between October 15 and November 15, 2020, using a composite online survey including the Vaccine Attitudes Examination Scale in addition to questions on sociodemographic correlates and the role of healthcare professionals. The vaccine hesitancy rate was 19.5%. The main reasons for willingness to vaccinate included understanding the nature of disease and role of vaccination, in addition to information provided by physicians. Fears mainly centered around vaccine safety. Vaccine hesitators were more likely to be non-Qatari and having received the influenza vaccine at least once. Gender, marital status, socioeconomic status, educational level, and having completed childhood vaccinations were not associated with vaccine hesitancy. Efforts should be directed toward raising awareness of vaccine efficacy and safety profiles. Physicians should additionally be educated about their pivotal role in advocating vaccine acceptance. We recommend reassessing vaccine hesitancy and its associated factors following a year of campaigning and vaccine administration to identify and target vulnerable groups. Other Information Published in: Medicine License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1097/md.0000000000029741